Analisis Faktor Faktor Yang Memengaruhi Minat Penggunaan Electronic Money dan Munculnya Cashless Society di Indonesia - Mohammad Rafki Nazar; Utari Arifah; Serena Maharani Fitri; Syifa’ Aulia Santika Putri; Muhammad Pradiptya Ramadianto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to analyze the use of electronic money which has a negative impact on society and weaknesses or deficiencies in the use of electronic money. The research method used was to conduct research on respondents using the Google form and also complemented by several sources from trusted websites, books, and relevant journals.